2017
DOI: 10.3389/fncel.2017.00382
|View full text |Cite
|
Sign up to set email alerts
|

Secretin Modulates the Postnatal Development of Mouse Cerebellar Cortex Via PKA- and ERK-dependent Pathways

Abstract: Postnatal development of the cerebellum is critical for its intact function such as motor coordination and has been implicated in the pathogenesis of psychiatric disorders. We previously reported that deprivation of secretin (SCT) from cerebellar Purkinje neurons impaired motor coordination and motor learning function, while leaving the potential role of SCT in cerebellar development to be determined. SCT and its receptor (SCTR) were constitutively expressed in the postnatal cerebellum in a temporal and cell-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(24 citation statements)
references
References 55 publications
2
22
0
Order By: Relevance
“…In the cerebellum, newly generated granular cells in the EGL progressively migrate inward to reside within the destined positions of the internal granular layer (IGL) where further maturation follows. Similar phenotypes also occur in the cerebellar IGL where s higher number of apoptotic cells was found in SCT knockout mice than that in their wild-type littermates (Wang et al, 2017). Based on current knowledge, however, it is still unclear whether the poor survival rate of granular cells is due to the lack the neurotrophic factors that are needed for survival, or due to the deficits for their inability to establish appropriate synaptic projections with target neurons as a consequence of their premature migration (Wang et al, 2017).…”
Section: Effects Of Sct On Cell Survival and Neural Developmentmentioning
confidence: 88%
See 2 more Smart Citations
“…In the cerebellum, newly generated granular cells in the EGL progressively migrate inward to reside within the destined positions of the internal granular layer (IGL) where further maturation follows. Similar phenotypes also occur in the cerebellar IGL where s higher number of apoptotic cells was found in SCT knockout mice than that in their wild-type littermates (Wang et al, 2017). Based on current knowledge, however, it is still unclear whether the poor survival rate of granular cells is due to the lack the neurotrophic factors that are needed for survival, or due to the deficits for their inability to establish appropriate synaptic projections with target neurons as a consequence of their premature migration (Wang et al, 2017).…”
Section: Effects Of Sct On Cell Survival and Neural Developmentmentioning
confidence: 88%
“…One of the most extensively studied effects of SCT resides in its neuroprotective potency against apoptosis and in favor of cell survival. Physiologically, SCT deficiency results in excess apoptosis in the dentate gyrus (DG) of hippocampus (Jukkola et al, 2010) and the external granular layer (EGL) of cerebellum during early postnatal development (Wang et al, 2017). Using in situ Terminal deoxynucleotidyl transferase (TdT) dUTP Nick-End Labeling (TUNEL) assay, more apoptotic cells were found in these two subregions of SCT knockout mice where neural progenitor cells reside and undergo intensive proliferation.…”
Section: Effects Of Sct On Cell Survival and Neural Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…For investigating the molecular and cellular mechanism, secretin has been found to induce the spinogenesis of hippocampal neurons (Nishijima et al, 2006), and the deficiency of secretin impairs both the induction and maintenance of LTP in hippocampal neurons (Yamagata et al, 2008). We recently found that secretin could potentiate postnatal proliferation and migration of cerebellar granular neurons (Wang et al, 2017) and potentiate inhibitory postsynaptic currents (IPSCs) of cerebellar Purkinje neurons (Yung et al, 2001), adding further knowledge to the neural plasticity modulation by secretin. As the secretin receptors mostly belong to GPCR family, the activation of cyclic AMP (cAMP)-protein kinase A (PKA) pathway in brain regions have been established for secretin (Pang et al, 2015).…”
Section: Secretinmentioning
confidence: 99%
“…Alternatively, other downstream pathways such as cAMP-response element -binding protein (CREB) activation (Mak et al, 2019) can initiate the translation of synaptic proteins to modulate long-term plasticity and memory functions. The extracellular signal regulated kinase (ERK) pathway is also involved upon secretin stimulation (Wang et al, 2017). In sum, secretin is one possible modulator of social functions, and is worth further investigation to reveal detailed circuitry effects.…”
Section: Secretinmentioning
confidence: 99%